2006
DOI: 10.1176/appi.ap.30.4.325
|View full text |Cite
|
Sign up to set email alerts
|

Choosing a Career in Psychiatry: Influential Factors Within a Medical School Program

Abstract: Although limited by small sample size and potential recall biases, this study suggests that positive clerkship experiences and participation in psychiatry electives may be modifiable programmatic factors that could enhance recruitment to psychiatry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(28 citation statements)
references
References 15 publications
1
27
0
Order By: Relevance
“…Current literature highlights several contributors to the recruitment challenge, including medical and pre-medical school influences, financial imperatives, patient and discipline stigma, and lifestyle implications 5. The psychiatry recruitment literature largely includes retrospective perspectives of current psychiatry resident trainees and junior undergraduate medical students earlier in their training 68…”
mentioning
confidence: 99%
“…Current literature highlights several contributors to the recruitment challenge, including medical and pre-medical school influences, financial imperatives, patient and discipline stigma, and lifestyle implications 5. The psychiatry recruitment literature largely includes retrospective perspectives of current psychiatry resident trainees and junior undergraduate medical students earlier in their training 68…”
mentioning
confidence: 99%
“…Previous research has suggested that clinical encounters are pivotal in influencing students and changing career intentions. 10 However, our carefully designed programme suggests that patient contact in this type of event is not essential. We believe this is because the programme compensated by focusing on bringing to life patient experiences through cases, highlighting recovery, emphasising an empathic approach and having workshops that included case studies that embodied the role of the psychiatrist in patient journeys.…”
Section: Discussionmentioning
confidence: 99%
“…The primary UPE objective at UT also includes producing students who can meet national standards [12]. A parallel objective at UT is also to provide a competitive, wellsupported curriculum in order to stimulate interest and motivate students to pursue a career in psychiatry [13][14][15].…”
Section: Upe At Gxmu and Utmentioning
confidence: 99%